Experimental quantum simulation of superradiant phase transition beyond no-go theorem via antisqueezing - Chen, Xi; Wu, Ze; Jiang, Min; Lü, Xin-You; Peng, Xinhua; Du, Jiangfeng (Nature communications, 2021)
The superradiant phase transition in thermal equilibrium is a fundamental concept bridging statistical physics and electrodynamics, which has never been observed in real physical systems since the first proposal in the 1970s. The existence of this phase transition in cavity quantum electrodynamics systems is still subject of ongoing debates due to the no-go theorem induced by the so-called A 2 term. Moreover, experimental conditions to study this phase transition are hard to achieve with current accessible technology. Based on the platform of nuclear magnetic resonance, here we experimentally simulate the occurrence of an equilibrium superradiant phase transition beyond no-go theorem by introducing the antisqueezing effect. The mechanism relies on that the antisqueezing effect recovers the singularity of the ground state via exponentially enhancing the zero point fluctuation of system. The strongly entangled and squeezed Schrödinger cat states of spins are achieved experimentally in the superradiant phase, which may play an important role in fundamental tests of quantum theory and implementations of quantum metrology. Quantum simulation allows to investigate otherwise inaccessible physical scenarios. Here, the authors simulate a quantum Rabi model using nuclear spins, including the A2 term and an anti-squeezing term, which allows them to see signatures of a superradiant phase transition in the simulated system.